Experimental Ka-Band Ground-Based SAR System - Bezvesilniy, O.O.; Vavriv, D.M.; Volkov, V.A.; Kravtsov, A.A.; Bulakh, E.V.; Vinogradov, V.V.; Sekretarov, S.S. (Радиофизика и радиоастрономия, 2015)
An experimental ground-based synthetic aperture radar (GB-SAR) system operating at Ka-band has been developed. The system is designed to be operated from a top a hill or from a building roof, etc. for imaging the underlying ground terrain. The radar hardware system, operating mode and original data processing techniques are described in the paper. A high-duty-cycle long-LFM-pulse mode (quasi-continuous mode) has been used. An effective adaptive matched filtering for range compression has been introduced that provides high dynamic range and high coherency for the radar system. A prominent point processing autofocus has been implemented for the precise estimation and compensation of motion errors of the radar platform. The achieved performance of the GB-SAR system is illustrated with experimental data. Разработана экспериментальная наземная радиолокационная система с синтезированной апертурой (РСА-система), работающая в Ka-диапазоне длин волн. Система спроектирована для работы с вершины холма или крыши здания и т. п. для построения изображений нижерасположенной местности. В статье описана аппаратная часть радиолокатора, режим работы и оригинальные методы обработки данных. Применен режим работы с длинными импульсами с линейной частотной модуляцией с высокой скважностью (квази-непрерывный режим). Предложена техника сжатия импульсов с эффективным адаптивным согласованным фильтром, которая обеспечивает высокий динамический диапазон и высокую когерентность радиолокационной системы. Для точной оценки и компенсации ошибок движения радиолокационной платформы применен метод автофокусировки по сигналам от ярких точек. Достигнутая эффективность наземной РСА-системы проиллюстрирована на экспериментальных данных. Розроблено експериментальну наземну радіолокаційну систему з синтезованою апертурою (РСА-систему), яка працює в Ka-діапазоні довжин хвиль. Систему спроектовано для роботи з вершини пагорба або даху будівлі тощо для побудови зображень нижче розташованої місцевості. В статті описано апаратну частину радіолокатора, режим роботи і оригінальні методи обробки даних. Застосовано режим роботи з довгими імпульсами з лінійною частотною модуляцією з високою скважністю (квазі-неперервний режим). Запропоновано техніку стискання імпульсів з ефективним адаптивним узгодженим фільтром, що забезпечує високий динамічний діапазон та високу когерентність радіолокаційної системи. Для точної оцінки і компенсації помилок руху радіолокаційної платформи використано метод автофокусування за сигналами від яскравих точок. Досягнута ефективність наземної РСА-системи проілюстрована на експериментальних даних.